16-MEMBER JAPANESE DELEGATION PARTICIPATED IN SUSTAINABILITY PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 29 August 2016 – Universiti Sains Malaysia (USM) through the Regional Centre of Expertise (RCE) Penang, JapanMalaysia Association and the Environmental Restoration and Conservation Agency of Japan (ERCA) has successfully organised a programme known as ERCA: Overseas Training Course 2016, which is a collaborative effort between Japan and Malaysia.